Infection Rate of Helicobacter pylori Infected among Fecal Occult Blood Test Positive (Patients) of Annual Physical Examination at Roi Et Hospital - Kunyakham, Wichak (Srinagarind Medical Journal, 2023)
Background and Objective: Helicobacter pylori (H. pylori) infection is associated with peptic ulcer, gastritis, duodenal ulcer as well as the occurrence of gastric cancer. The objective of this study was to investigate the infection rate of H. pylori in those who had fecal occult blood test (FOBT) positive of annual physical examination at Roi Et Hospital. Method: This study was a retrospective descriptive study. All data were collected from medical records of 235 FOBT positive cases who attended an annual physical examination at Roi Et Hospital between 1 January 2020 and 31 December 2022. All of them were FOBT positive, underwent with esophagogastroduodenoscopy (EGD), and positive for H. pylori infection by Rapid urease test. Descriptive statistics were used for all data analysis. Results: All of 235 cases underwent with EGD, most of them were female 56.17%, mean age 54.22 years. Hypertension was major underlying disease (23.40%). The EGD examination revealed that upper gastrointestinal abnormal 98.29% (231 cases), gastritis 77.87%, gastric polyp 6.81%, hemorrhagic gastritis 4.68%, hiatal hernia 2.55%, and duodenitis 2.13%. The H. pylori rapid urease tests were positive in 228 cases (97.02%). All cases with H. pylori infection were treated. Conclusion: This study found the infection rate of H. pylori infected was 97.02 % and the EGD examination found out that upper gastrointestinal abnormality was 98.29%. All cases with H. pylori infection and upper gastrointestinal abnormalities were treated.